DIAGNOSTICS OF LOCAL MAGNETIC FIELDS IN SOLAR FLARES USING FeI 5383 AND MgI 5528 LINES - Lozitsky, V. G.; Lozitsky, O. V. (Одеські астрономічні публікації, 2014)
Main purpose of the present work is to estimate upper limit of the local magnetic field strength in solar flares using spectral lines FeI 5383 and MgI 5528. These lines like FeI 5233 have low Landé factors (1.12 and 1.00, respectively) and relatively large spectral width (0.2–0.3 Ǻ). On this account, even in a case of very strong fields (3-4 kG) they must show the simple picture of the Zeeman splitting, with parallel to each other the bisectors of profiles I+V and I – V. In actual fact, another picture was found for nine flares: bisectors of these lines have maximums of splitting on certain distances from line center, what must not be in the homogeneous magnetic field. In particular, both lines have peak of bisector splitting on distance 150–170 mǺ from line center. If we assume the Zeeman nature of named peculiarities then necessary fields are 11.2 kG for FeI 5383 and 10.5-11.2 kG for MgI 5528. Likely, this agreement of field values is a new argument to reality of such very strong magnetic fields in flares.